Preliminary assessment of habitat characteristics of woodland caribou calving areas in the Claybelt region of Québec and Ontario, Canada - Lantin, Émilie; Drapeau, Pierre; Paré, Marcel; Bergeron, Yves (Rangifer, 2003)
Woodland caribou (Rangifer tarandus caribou) require a diversity of forested habitats over large areas and may thus be particularly affected by the large-scale changes in the composition and age-class distribution of forest landscapes induced by the northern expansion of forest management. In this study we examine habitat characteristics associated to the use of calving areas by woodland caribou females and calves at different spatial scales. Thirty females were captured and collared with Argos satellite transmitters that allowed to locate 14 calving areas. Field surveys were conducted at each of these areas to measure the landscape composition of forest cover types and local vegetation characteristics that are used for both forage conditions and protection cover. At the scale of the calving area, univariate comparisons of the amount of forest cover types between sites with and without calves showed that the presence of calves was associated to mature black spruce forest with a high percent cover of terrestrial lichens. Within calving grounds, univariate comparisons showed that vegetation features like ericaceans and terrestrial lichens, that are important food resources for lactating females, were more abundant in calving areas where females were seen with a calf in mid-July than in areas where females were seen alone. The protection of the vegetation cover against predators was however similar between calving areas with or with¬out a calf. Logistic regression results also indicated that vegetation characteristics associated to forage conditions were positively associated to calf presence on calving grounds. Our results suggest that foraging conditions should be given more attention in analyses on habitat requirements of woodland caribou.